Board of Directors and Firm Performance: Do Family and ForeignOwnership A Double-Edged Sword? - Armadani; Zahroh Naimah (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study aims to empirically prove the role of family and foreign ownership in moderating the influence of the board of directors on company performance.Methods: The analysis technique used is moderated regression analysis (MRA). The study was conducted on companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, with a total of 752 observations.Findings: The results of this study found that, empirically, gender and board size have a positive effect on a company’s financial performance. Family ownership does not increase the positive effect of gender and board size on a company’s financial performance. Foreign ownership increases the positive effect of gender and board size on a company’s financial performance.Novelty: This research makes a significant contribution to science, particularly in accounting. It analyzes and provides comprehensive empirical evidence on the relationship between family and foreign ownership, the board of directors, and firm performance, especially in the study model and an analytical approach that divides the period based on the COVID-19 outbreak.Keywords: Board of Directors, Family Ownership, Foreign Ownership, Corporate Financial Performance.